ChemInform Abstract: A Modified Procedure for the Palladium Catalyzed Borylation/Suzuki—Miyaura Cross‐Coupling of Aryl and Heteroaryl Halides Utilizing Bis‐boronic Acid. Issue 47 (November 2015) - Molander, Gary A.; Trice, Sarah L.J.; Tschaen, Brittany
Abstract: Notable advantages of the improved one‐pot protocol using ethylene glycol as an additive are increased yields, shorter reaction times and a broader substrate scope.